1993
DOI: 10.1002/hep.1840170113
|View full text |Cite
|
Sign up to set email alerts
|

Depression of Drug-metabolizing Activity in the Human Liver by Interferon-β

Abstract: The depressant effect of interferon beta on drug-metabolizing activity in the human liver was investigated. Seven patients with chronic hepatitis C were treated with interferon beta at doses of 3 x 10(6) to 9 x 10(6) IU/day for 8 wk. The activities of 7-methoxycoumarin O-demethylase and 7-ethoxycoumarin O-deethylase in specimens obtained by liver biopsy were examined before and after interferon treatment. Theophylline pharmacokinetics were also examined before and after interferon treatment. Interferon beta tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Williams et al (1987) reported already in 1987 that 1 day after a single intramuscular injection of IFN-α in five patients with chronic hepatitis B and four healthy volunteers, clearance of the CYP1A2 substrate theophylline was significantly reduced (30–80%). A 26% reduction in clearance of theophylline was also observed in patients with hepatitis C after IFN-β treatment, with a corresponding increase in terminal half-life of about 40% (Okuno et al, 1993). Additionally IFN-α administration in patients with hepatitis B has been shown to cause a minor decrease of erythromycin metabolism (15%), as determined by ERMBT (Craig et al, 1993), and patients monitored on warfarin needed a dose reduction when IFN-α-2b and IFN-β were given (Adachi et al, 1995).…”
Section: Drug Interaction With Therapeutic Proteinsmentioning
confidence: 91%
“…Williams et al (1987) reported already in 1987 that 1 day after a single intramuscular injection of IFN-α in five patients with chronic hepatitis B and four healthy volunteers, clearance of the CYP1A2 substrate theophylline was significantly reduced (30–80%). A 26% reduction in clearance of theophylline was also observed in patients with hepatitis C after IFN-β treatment, with a corresponding increase in terminal half-life of about 40% (Okuno et al, 1993). Additionally IFN-α administration in patients with hepatitis B has been shown to cause a minor decrease of erythromycin metabolism (15%), as determined by ERMBT (Craig et al, 1993), and patients monitored on warfarin needed a dose reduction when IFN-α-2b and IFN-β were given (Adachi et al, 1995).…”
Section: Drug Interaction With Therapeutic Proteinsmentioning
confidence: 91%
“…In this case, interferons [10], interleukin-I [13], and tumor necrosis factor [9] secreted by activated MP act as inhibitory monokines. The amount and type of synthesized products depend on the nature, dose, molecular weight, physical properties, chemical composition, and structure of the stimulating substance, as well as on the reciprocal regulation by MP mediators.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that administration of TNF, IL-1, IFN-y and IL-2 results in reduced levels of cytochromes P-450 in a dose-dependent manner (30,33). Furthermore, clinical studies with these agents have reported liver toxicity, including altered drug clearance, as a side effect (34). This could be a direct consequence of altered enzymatic activities.…”
Section: Discussionmentioning
confidence: 96%